PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP EARNINGS RESPONSE COEFFICIENT - Anggreni Dian Kurniawati (Jurnal Akuntansi Bisnis, 2014)
A good financial reporting quality is reflected in a good quality of earnings. Earnings Response Coefficient (ERC) measuring the power of relationships between accounting earnings and the stock price or usually called earning quality measurement. This study examines the effects of characteristic of the Asian and European firms on ERC. The characteristics based on four parameters: earnings persistence, leverage, firm size, and accruals quality. This study focus on Asian and European multinational companies which cross-listed in New York Stock Exchange (NYSE). They can be said that they have the same level with domestic companies in United States of America (USA), so that is a possibility of their earning quality will be responded to the same by investor without considering the characteristics of their companies and their state. This study was conducted in thirty six European manufacturing companies and fifty manufacturing companies cross-listed on the NYSE during the period 2008-2011. The data was collected by purposive sampling. Multiple linear regression is used in testing the data of this study. This study provided evidences that earnings persistence, leverage, and accruals quality were positively affected the ERC both in Asian and European companies. While the firm size positively affected the ERC in Asian companies, but negatively affected the ERC in European companies. The difference was due to by the effect of the difference in quality companies that be responded differently by investors in the capital market for both companies. This study is expected to contributing positively investors for a better decision making.